Neuroprawo: próba zaklasyfikowania dowodu w postaci obrazowania mózgu z badania fMRI w polskim procesie karnym - Krupa, Magdalena (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
“Neurolaw” is an interdisciplinary field that combines issues related to law and other sciences such as psychology or criminology. The emergence of this field is associated with the rapid development of new techniques and research methods. This article focuses on the possibility of using functional magnetic resonance imaging in a criminal trial. To prove whether it is possible to use an fMRI image as evidence in a criminal trial, linguistic, systemic, and functional interpretations of given legal provisions were presented. The only reasonable solution seems to be to admit such evidence as a part of psychiatric expert evidence or to conduct an fMRI test during an expert examination using technical means which allow controlling the unconscious reactions of the subject’s organism.